Selective cytoprotective effect of histamine on doxorubicin-induced hepatic and cardiac toxicity in animal models - Martinel Lamas, Diego J. (2015)
Fil: Martinel Lamas, Diego J. Universidad de Buenos Aires. Facultad de Farmacia y Bioquímica; Argentina